Acupuncture increases parasympathetic tone, modulating HRV − Systematic review and meta-analysis - Sz. Hamvas; P. Hegyi; Sz. Kiss; Sz. Lohner; D. McQueen; M. Havasi (Elsevier, 2023)
Introduction: An increasing number of studies have demonstrated that acupuncture can influence Autonomic Nervous System functions. Heart Rate variability (HRV) is one widely used marker of autonomic activity. The main objective of this systematic review is to critically assess the evidence from randomized clinical trials (RCTs) regarding the effect of acupuncture on HRV as compared to placebo methods. Method: EMBASE, Pubmed, The Cochrane Library, Web of Science, Scopus electronic databases were searched until 9 September 2020 for RCTs in which human subjects were treated with needle acupuncture using acupoints of the body without electric stimulation. Results: The searches identified 1698 potentially relevant articles, 9 RCTs were included. The statistical analysis of the available data showed that the changes between pre and post treatment HF (high frequency) and LF/HF (high frequency/low frequency) values in Verum group were significant, while there were no significant changes in these parameters in Sham groups. Conclusion: the results of this meta-analysis suggest that real acupuncture has superior effect over placebo acupuncture in increasing parasympathetic tone and in this way may improve physical well-being. Due to the quality of primary studies and degree of heterogeneity the results should be interpreted cautiously.